Answer:
h(4) = –12
Step-by-step explanation:
⇒ What the question is asking is that when the function h(n) = –2n(2) + 4 is h(4), what will the function repond to when solving for h(4)? So, solve for the function h(4):
h(4) = –2n(2) + 4
⇒ Since n was replaced with 4 in the function h(4), substitute any n for 4 into the function:
h(4) = –2(4)(2) + 4
⇒ Simplify:
h(4) = –16 + 4
⇒ Solve:
h(4) = –12
<u>Answer:</u> h(4) = –12
<em>I hope you understand and that this helps with your question! </em>:)
Answer:
5
Step-by-step explanation:
it is 5 because you do 1+4=5
I would belive its great because if you have 4/5 of a pie compared to 7/12 of a pie having 4/5 would be more of the pie , I hope that helped that's how I have to think about fractions
Feet
_____
second
10 feet
________
16 second
equals
.625 feet per second